Cultural foundations of global health: a critical examination of universal child feeding recommendations - Gabriel Scheidecker; Leberecht Funk; Nandita Chaudhary; Bambi L. Chapin; Wiebke J. Schmidt; Christine El Ouardani (Global Health Research and Policy)
Abstract There has been a rising call to decolonize global health so that it more fully includes the concerns, knowledge, and research from people all over the world. This endeavor can only succeed, we argue, if we also recognize that much of established global health doctrine is rooted in Euro-American beliefs, values, and practice rather than being culturally neutral. This paper examines the cultural biases of child feeding recommendations as a case in point. We argue that the global promotion of Responsive Feeding—a set of allegedly best practices for child feeding promulgated by the WHO and others—is based on a tacit conviction that certain Western middle-class feeding practices are universally best, along with a promise that future evidence will demonstrate their superiority. These recommendations denounce feeding practices that diverge from this style as Non-Responsive Feeding, thereby pathologizing the many valued ways of feeding children in communities all over the world without sound scientific evidence. Drawing on ethnographic research, we show that there is a wide variety in feeding practices around the world and these are closely interlinked with the understandings and priorities of caregivers, as well as with favored forms of relationships and ways of maintaining them. For global health nutrition interventions to be justified and effective, they would need to be based on more pertinent, culturally responsive research than they currently are. We suggest the use of ethnographic research as an important tool in building empirically grounded, epistemically inclusive, and locally meaningful approaches to improving nutritional support for children in communities around the world and to global health efforts more broadly.